Comparative study of kaolin and bentonite as potential materials for halal sertu in healthcare application - Che Ahmad, Aminudin; Al-Azmi, Abdul Rahman; Ahmad, Zuraida; Samat, Noorasikin; Sarifuddin, Norshahida; Awang, Mohd Shukrimi (Lokman Hekim Oniversites, 2024)
This study explores the suitability of kaolin and bentonite clays for halal Sertu solutions in healthcare applications, specifically for equipment cleansing using the spraying technique. Addressing challenges arising from dog and wild boar bites, the research emphasizes adherence to Islamic jurisprudence, utilizing water and specific soils for formulation. Structural properties of kaolin, with its ordered crystal lattice, and bentonite, known for its swelling capabilities, are analyzed through Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD). The study also investigates their morphology using Scanning Electron Microscopy (SEM). Results indicate that kaolin, with its higher crystallinity and organized structure, exhibits enhanced homogeneity and stability in healthcare-relevant solutions. In contrast, bentonite's more disordered structure may pose challenges in achieving uniform dispersion. The findings contribute crucial insights for developing a standardized, halal-compliant Sertu product, aligning with healthcare standards, equipment specifications, and regulatory guidelines for safe and quality industrial applications.